C- and N-truncated antimicrobial peptides from LFampin 265 - 284: Biophysical versus microbiology results - Regina Adão; Kamran Nazmi; Jan G.M. Bolscher; Margarida Bastos (Wolters Kluwer Medknow Publications, 2011)
Lactoferrin is a glycoprotein with two globular lobes, each having two domains. Since the discovery of its antimicrobial properties, efforts have been made to find peptides derived from this protein showing antimicrobial properties. Most peptides initially studied were derived from Lactoferricin B, obtained from the protein by digestion with pepsin. More recently, a new family of antimicrobial peptides (AMPs) derived from Lactoferrin was discovered by Bolcher et al, and named Lactoferrampin (LFampin). The original sequence of LFampin contained residues 268 - 284 from the N1 domain of Lactoferrin. From this peptide, the Bolscher's group synthesized a collection of peptides obtained by extension and / or truncation at the C or N-terminal sides, in order to unravel the main structural features responsible for antimicrobial action. Here, we present results for three of these peptides, namely LFampin 265 - 284, LFampin 265 - 280, and LFampin 270 - 284. The peptides were tested against bacteria (E. coli and S. sanguinis), fungi (C. albicans), and model membranes of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC), 1,2-dimyristoyl-sn-glycero-3-[phospho-rac-(1-glycerol)] (DMPG), and their mixtures at a ratio of 3 : 1 (DMPC : DMPG (3 : 1)). The ability to adopt a helical conformation was followed by a circular dichroism (CD), and the perturbation of the gel to the liquid-crystalline phase transition of the membrane was characterized by differential scanning calorimetry (DSC). Distinct behavior was observed in the three peptides, both from the microbiology and model membrane studies, with the biophysical results showing excellent correlation with the microbiology activity studies. LFampin 265 - 284 was the most active peptide toward the tested microorganisms, and in the biophysical studies it showed the highest ability to form an a-helix and the strongest interaction with model membranes, followed by LFampin 265 - 280. LFampin 270 - 284 was inactive, showing marginal secondary structure and no interaction with the pathogen model membranes.